Identification of molecular changes and virulence determinants in a mouse adapted influenza virus A/FM/1/47. - Smeenk, Cecilia (University of Ottawa (Canada), 1994)
The human influenza virus A/FM/1/47 (FM) was mouse-adapted by serial lung passage to produce the more virulent variant A/FM/1/47-MA (FM-MA). Previous genetic analysis identified four genome segments, 4, 5, 7 and 8 that are statistically associated with virulence. The aim of this investigation was first, to find the mutations on these four genome segments and then to determine a role for these changes in disease production. Upon sequencing segments 4 and 7, single amino acid replacements were found at amino acid 47 of the HA2 subunit of the hemagglutinin (HA) and at amino acid 139 of the matrix protein (M1). Segments 5 and 8 had not mutated on mouse-adaption. Viral growth kinetics were studied both in the mouse lung and in cell culture with MDCK cells. For viral pathology, standard hematoxylin, phloxine, saffron staining of formalin fixed sections, fluorescent antibody labelling of frozen sections and flow cytometric analysis for infected cells and immune cell recruitment was used to detect differences between the viruses. The matrix protein has a role in both replication and pathology and its coding change can be observed as a shift on SDS-PAGE. It was shown that viruses containing the matrix protein of FM-MA could replicate as quickly and to as high a titer as FM-MA itself. In pathology, it was apparent that segment 7 contributes to the early onset of interstitial pneumonia and that these reassortants can infect a greater number of cells than FM or the segment 4 reassortants. The parental FM-MA strain infects more cells in the lung and is more virulent than FM X FM-MA reassortants containing segments 4 and 7. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.